Preparation method of self-repairing cellulose insulation paper doped with ultraviolet light triggered microcapsules
By embedded in the micro -capsule structure triggered by ultraviolet light in the cellulose insulation paper, the active identification and instant repair of tiny damage were achieved, solving the problem of traditional insulating paper in the prevention and control of damage expansion, significantly improved the durability of insulation paper And stability.
Patent Information
- Application Number
- CN202411743608.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-30
AI Technical Summary
Traditional cellulose insulating paper faces the difficulties of difficult detection of minor damage and the prevention and control of damage expansion, which has threatened the safe operation of the power grid.
Self -repairing fiber insulation paper preparation methods that use doped ultraviolet light to trigger microcapsules are used to achieve active identification and instant repairs of micro -damage through the micro -capsule structure triggered by ultraviolet light in cellulose. The micro -capsule is composed of FE3O4@SiO2 nanoparticles modified repair agent and TIO2 nanopartal polymer formaldehyde prefabricated. Migration of micro -capsules with directional magnetic fields is used to improve its uniform distribution in the insulation paper.
The self -repair of insulation paper is achieved, significantly improved its durability and stability, extended the service life, and reduced the risks caused by accidents such as insulation.
Smart Images

Figure CN119372962A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of high voltage and insulation technology, and in particular to a method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules. Background Art
[0002] Since the 1890s, natural cellulose-based insulating paper has become an indispensable insulating material in oil-immersed power equipment due to its low cost, excellent mechanical strength, easily controlled size, excellent electrical performance after oil immersion, and environmental friendliness. Although the field of insulating materials has made significant progress and changes today. In the vast arena of electrical insulation, the stable operation of the power grid is inseparable from the support of reliable and durable insulating materials. However, during the preparation, installation and long-term operation of insulating paper, due to the limitations of process conditions, long-term electrothermal stress and excessive physical deformation, micro defects such as microcracks and electrical dendrites are often inevitably formed inside. These tiny damages hidden deep in the material will gradually expand under the continuous action of factors such as electric field and high temperature, which may distort the electric field distribution and induce partial discharge, posing a severe challenge to the safe operation of the power grid.
[0003] What is even more difficult is that these minor damages are often difficult to detect in time with existing technologies. Even if they can be discovered, the only option is to take extreme measures such as replacing the entire material. This not only means great difficulty in power outage construction in busy areas, but also requires a lot of manpower, material and financial resources. At the same time, it is accompanied by the generation of a large amount of waste, which increases the pressure on solid waste treatment and waste of resources. Therefore, if the insulating material can have self-repair capabilities, that is, it can automatically sense and start the repair mechanism when the damage first appears, and promptly curb the spread of the damage and prevent it from further deteriorating, then this will hopefully effectively restore the material performance and greatly reduce the risk of damage to electrical equipment and the probability of accidents.
[0004] Microcapsule external aid self-healing materials are an innovative solution that emerged under this background. The core principle is to embed microcapsules containing repair agents into the material. Once damage occurs inside the material, the stress concentration at the damaged part will cause the microcapsules to rupture, and the released repair agent will then solidify under external stimulation, thereby filling and repairing the damaged structure, achieving self-repair and regeneration of the material. However, there are few studies in the field of microcapsule self-healing materials that use ultraviolet light to trigger automatic recognition and immediate self-repair. Summary of the invention
[0005] The present invention is dedicated to solving the problem of difficult detection of tiny damage and prevention of damage expansion faced by traditional cellulose insulating paper in application, and innovatively proposes a method for preparing self-repairing cellulose insulating paper doped with ultraviolet light-triggered microcapsules. Compared with traditional cellulose insulating paper, the self-repairing insulating paper prepared by the present invention achieves active identification and immediate repair of tiny damage by cleverly embedding a microcapsule structure triggered by ultraviolet light, which not only enhances the durability of the insulating paper, but also substantially extends its service life, significantly improves its stability and safety in complex environments, and brings revolutionary progress to the field of high voltage and insulating materials. The technical solution of the present invention is as follows:
[0006] The prepared microcapsules are added into the process of pulping and papermaking of insulating paper, and the microcapsules are migrated by using a directional magnetic field; wherein the microcapsules include a microcapsule core material and a microcapsule wall material, the core material is made by modifying a repair agent with Fe3O4@SiO2 nanoparticles, and the wall material is made by modifying a polyurea formaldehyde prepolymer with TiO2 nanoparticles; the repair agent includes epoxy acrylate, neopentyl glycol diacrylate, and a photoinitiator; the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone.
[0007] The present invention provides a method for preparing self-repairing cellulose insulating paper doped with ultraviolet light-triggered microcapsules, which specifically comprises the following steps:
[0008] (1) synthesizing Fe3O4 nanoparticles by hydrothermal reaction: dissolving styrene sulfonic acid-maleic anhydride copolymer (PSSMA), FeCl3·6H2O and NaAc in ethylene glycol, wherein the mass ratio of PSSMA:FeCl3·6H2O:NaAc is 1-2:1:1-2, the concentration of FeCl3·6H2O is 0.2-0.5 mol / L, the concentration of NaAc is 0.2-0.5 mol / L, and the concentration of PSSMA is 0.1-0.5 mol / L, stirring is performed with a magnetic stirrer, and then transferring to a hydrothermal reactor to obtain Fe3O4 nanoparticles after sufficient reaction; after the hydrothermal reaction is completed, separating the synthesized Fe3O4 nanoparticles with a magnetic material;
[0009] (2) Synthesis of Fe3O4@SiO2 nanoparticles: Fe3O4 nanoparticles were mixed with anhydrous alcohol, deionized water and ammonia water, and ultrasonically treated to ensure proper dispersion, and then tetraethyl orthosilicate (TEOS) was added in an amount of 0.3-0.5%, and ultrasonic chemical treatment was continued. After the reaction was complete, the mixture was washed and dried to obtain Fe3O4@SiO2 nanoparticles;
[0010] (3) Preparing a microcapsule core material: Fully mixing epoxy acrylate (EA), neopentyl glycol diacrylate (NPGDA) and photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA), EA:NPGDA:DMPA=18-20:18-20:1-2, reacting for 0.5-1.5h to obtain a repair agent; modifying the Fe3O4@SiO2 nanoparticles synthesized in step (2) in the repair agent by ultrasonic dispersion to obtain a microcapsule core material;
[0011] (4) preparing TiO2 emulsion: dispersing amphoteric TiO2 nanoparticles in deionized water, wherein the concentration of the amphoteric TiO2 nanoparticles is 0.7-1.5 g / 100 mL, adding the microcapsule core material obtained in step (3) to the TiO2 aqueous solution, and emulsifying the solution at room temperature to obtain a TiO2 emulsion;
[0012] (5) preparing microcapsule wall material: urea, formaldehyde and deionized water are mixed, the pH is adjusted to 8-9, and then heated in a water bath to obtain a polyurea-formaldehyde prepolymer, and then amphoteric TiO2 nanoparticles are dispersed in the polyurea-formaldehyde prepolymer by ultrasonic dispersion to obtain a TiO2-modified polyurea-formaldehyde prepolymer;
[0013] (6) preparing microcapsules: adding the TiO2 emulsion, ammonium chloride and resorcinol prepared in step (4) to the TiO2-modified polyurea-formaldehyde prepolymer, adjusting the pH value to 3.8-4.2, heating in a water bath and stirring until the reaction is fully reacted to obtain microcapsules;
[0014] (7) beating and disintegrating the pulp sheet: tearing the pulp sheet into small pieces, placing it in a pulper, adding deionized water for beating and defibrating, and after defibrating to a beating degree of 43-48° SR, placing the pulp in a fiber disintegrator, adding deionized water for mechanical treatment, so that the fibers are dispersed in water without changing their original structural properties, and obtaining a pulp suspension;
[0015] (8) adding the microcapsules obtained in step (6) into deionized water, stirring and dispersing, and then mixing the dispersed microcapsule aqueous solution with the pulp suspension to obtain a microcapsule pulp suspension;
[0016] (9) pouring the microcapsule pulp suspension into a pulp storage chamber, migrating the microcapsules to a target area under the action of a directional magnetic field, performing a molding process using a filter screen, and obtaining a molded insulating paper hand sheet by pressing and drying;
[0017] (10) placing the formed insulating paper hand sheet into a calender for calendering to obtain the self-repairing cellulose insulating paper.
[0018] In step (1), the directional magnetic field is used to guide the microcapsules and improve the uniform distribution of the microcapsules in the insulating paper, so that the repair agent can be released more efficiently when damage occurs, thereby achieving a better self-repairing effect.
[0019] Preferably, in step (1), the magnetic material is a permanent magnet. The Fe3O4 nanoparticles generated by the hydrothermal reaction are magnetic, so they can be separated using a permanent magnet. This is the most commonly used and efficient method. However, in addition to permanent magnets, other magnetic materials (such as iron-containing magnetic molecules, magnetic separation columns, etc.) can also be used for separation. The key is that the material used can effectively separate the magnetic particles from the liquid. Although magnetic materials can theoretically be used for separation, their magnetic field strength, separation efficiency and material stability will affect the final separation effect.
[0020] Preferably, in step (2), the concentration of Fe3O4 is 0.8-0.9 g / 100 mL, the mass ratio of Fe3O4 to tetraethyl orthosilicate is 1:1-3, and the volume ratio of anhydrous alcohol, deionized water and ammonia water is 3.5-4.5:0.8-1.2:0.8-1.2. If the concentration of Fe3O4 is too high, it may cause particle aggregation and affect its stability; if the concentration is too low, it may lead to insufficient number of nanoparticles generated. The volume ratio of anhydrous alcohol, deionized water and ammonia water will also affect the dispersibility, reaction rate and surface structure of the nanoparticles, and thus affect the quality of the final Fe3O4@SiO2 nanoparticles. Therefore, the ratio of these solvents needs to be adjusted within a certain range to ensure the best nanoparticle quality and product performance.
[0021] Preferably, in step (1), after the hydrothermal reaction is completed, a permanent magnet is used to separate the synthesized Fe3O4 nanoparticles.
[0022] Preferably, in step (3), the concentration of Fe3O4@SiO2 nanoparticles in the repair agent is 3-7wt%.
[0023] Further preferably, in step (3), the concentration of Fe3O4@SiO2 nanoparticles in the repair agent is 5wt%.
[0024] Preferably, in step (4), the rotation speed is controlled at 600-1000 r / min during the emulsification treatment. The rotation speed during the emulsification treatment affects the uniformity of the TiO2 emulsion and the dispersion of the particles. Too high or too low a rotation speed may lead to uneven particles in the emulsion.
[0025] Preferably, in step (5), triethanolamine is used to adjust the pH to 8-9.
[0026] Preferably, in step (5), the concentration of the amphoteric TiO2 nanoparticles in the polyurea-formaldehyde prepolymer is 2-4 wt%.
[0027] Further preferably, in the step (5), the concentration of the amphoteric TiO2 nanoparticles in the polyurea-formaldehyde prepolymer is 3 wt%.
[0028] Preferably, in step (6), the mass ratio of TiO2 emulsion, ammonium chloride and resorcinol is 9-12:0.8-1.2:0.8-1.2.
[0029] Further preferably, in step (6), the mass ratio of TiO2 emulsion, ammonium chloride and resorcinol is 10:1:1.
[0030] If the TiO2 content is too low, the performance of the material cannot be effectively improved, while if it is too high, the microcapsule wall material may be too fragile. Ammonium chloride acts as a catalyst in this reaction, and adding too high a proportion may cause the reaction to be too violent. Resorcinol acts as a cross-linking agent in this reaction, which can improve the cross-linking degree and stability of the microcapsule wall material. Excessive amounts of resorcinol will cause the wall material to harden too much, reduce the operability of microcapsule preparation, and affect the self-repairing effect of insulating paper. Too little use may cause the wall material to be not strong enough or unstable.
[0031] Preferably, in step (6), the mechanical stirring speed in the water bath is controlled to be 800-1100 r / min. Too fast a stirring speed may cause the microcapsule wall material to break, while too slow a stirring speed may cause uneven dispersion. Accurately controlling the stirring speed can ensure the quality of the microcapsule wall material.
[0032] Preferably, in step (8), the mass ratio of pulp suspension to microcapsules is 23-28:1.
[0033] Further preferably, in step (8), the mass ratio of the pulp suspension to the microcapsules is 25:1.
[0034] Preferably, in step (8), the doping concentration of the microcapsules in the pulp suspension is 0.5-10 wt %.
[0035] Preferably, in step (10), the calendering treatment is a segmented hot pressing, and the specific steps include:
[0036] The first stage of hot pressing: preheating stage, the temperature range is 80-120℃, the pressure is 0.5-2MPa, and the duration is 2-5min; the second stage of hot pressing: high temperature curing stage, the temperature is set at 140-180℃, the pressure is about 3-5MPa, and the duration is 5-15min; the third stage of hot pressing: cooling and shaping stage, the temperature gradually drops to 60-90℃, the pressure is maintained at 2-3MPa, and the duration is 5-10min.
[0037] The above temperature and pressure parameters can be optimized and adjusted according to specific experimental or industrial production conditions. Different raw materials, pulp composition, microcapsule content and final use will lead to different specific temperature, pressure and time settings. The temperature and pressure control during the hot pressing process, especially the wall material of the microcapsule, may affect the mechanical properties and repair properties of the final paper, so these parameters need to be precisely controlled.
[0038] The beneficial effects of the present invention are:
[0039] 1. The present invention provides a method for preparing self-repairing cellulose insulating paper doped with ultraviolet light-triggered microcapsules. The present invention adds prepared microcapsules during the pulping and papermaking process of insulating paper, and uses a directional magnetic field to migrate the microcapsules. Among them, epoxy acrylate (EA), neopentyl glycol diacrylate (NPGDA) and photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) are used to synthesize the repair agent, and Fe3O4@SiO2 nanoparticles are added to modify the repair agent; urea and formaldehyde are mixed to synthesize the microcapsule wall material, and TiO2 nanoparticles are added to form a polyurea formaldehyde (PUF) / TiO2 hybrid shell.
[0040] 2. The present invention ingeniously embeds a UV-triggered microcapsule structure in cellulose to achieve active identification and immediate self-repair of minor damage to the insulating paper. Once the material is damaged, the microcapsules rupture to release the repair agent, which solidifies under UV light, thereby effectively filling and repairing the damage, significantly improving the durability and stability of the insulating paper. Due to the existence of the self-repair mechanism, the insulating paper can recover in time when facing minor damage, and also avoids the performance degradation caused by the expansion of damage, thereby substantially extending the service life of the insulating paper. By utilizing the navigation effect of Fe3O4@SiO2 nanoparticles, the insulating paper can also achieve a high degree of self-healing at low doping concentrations; the introduction of TiO2 nanoparticles effectively prevents the premature curing of the repair agent by UV light, ensuring its effective release when needed; at the same time, with the help of in-situ ultraviolet rays emitted by electric trees to induce the curing of the healing agent, the braking identification of the insulating paper and the self-healing of electrical damage to the insulating paper are achieved.
[0041] 3. The self-repairing insulating paper of the present invention can better resist the continuous effects of factors such as electric fields and high temperatures, reduce the risks of local discharge and electric field distortion, and provide more reliable protection for the safe operation of the power grid. Compared with the overall replacement of traditional insulating paper after damage, self-repairing insulating paper can reduce the frequency of material replacement and waste generation. It also has significant self-repairing ability, can effectively extend the service life, and greatly reduce the risks caused by accidents such as insulation breakdown. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0043] Figure 1 This is a flow chart for preparing the self-repairing insulating paper of the present invention;
[0044] Figure 2 This is a diagram showing the effect of the self-repairing of electrical damage to the self-repairing insulating paper of the present invention;
[0045] Figure 3 This is a comparison diagram of the breakdown field strength of the self-repairing insulating paper of the present invention with different microcapsule doping concentrations;
[0046] Figure 4 This is a comparison chart of the Young's modulus self-repairing efficiency of the self-repairing insulating paper of the present invention with different microcapsule doping concentrations;
[0047] Figure 5 This is a comparison chart of the dielectric constant self-repair efficiency of the self-repairing insulating paper of the present invention at different microcapsule doping concentrations. DETAILED DESCRIPTION
[0048] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention, etc. can be purchased from the market or can be prepared by existing methods.
[0049] The amphoteric nano-TiO2 used in the embodiment of the present invention is produced by Shanghai Maikun Chemical Co., Ltd., CAS No.: 1317-80-2.
[0050] Example 1
[0051] This embodiment provides a method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules, which specifically includes the following steps:
[0052] (1) Synthesis of Fe3O4 nanoparticles by hydrothermal reaction: 1 g of styrene sulfonic acid-maleic anhydride copolymer (PSSMA), 1 g of FeCl3·6H2O and 3 g of NaAc were dissolved in 40 mL of ethylene glycol, stirred with a magnetic stirrer, and then transferred to a hydrothermal reactor and heated to 200°C for reaction. After the reaction was complete, Fe3O4 nanoparticles were separated by a permanent magnet, washed with anhydrous alcohol and deionized water, and dried at 50°C under vacuum to obtain Fe3O4 nanoparticles;
[0053] (2) Synthesis of Fe3O4@SiO2 nanoparticles: 0.2 g of Fe3O4 nanoparticles were mixed with 160 mL of anhydrous alcohol, 40 mL of deionized water, and 40 mL of aqueous ammonia, and ultrasonicated to ensure proper dispersion. Then, 1 mL of tetraethyl orthosilicate (TEOS) was added and ultrasonic chemical treatment was continued. After the reaction was complete, the mixture was washed and dried to obtain Fe3O4@SiO2 nanoparticles.
[0054] (3) Preparation of microcapsule core material: 19.2 g of epoxy acrylate (EA), 19.2 g of neopentyl glycol diacrylate (NPGDA) and 1.6 g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) were fully mixed and reacted for 1 hour to obtain a repair agent; the Fe3O4@SiO2 nanoparticles synthesized in step (2) were modified by ultrasonic dispersion in the repair agent to obtain a microcapsule core material; the concentration of the Fe3O4@SiO2 nanoparticles in the repair agent was 5 wt%;
[0055] (4) preparing TiO2 emulsion: dispersing 2 g of amphoteric TiO2 nanoparticles in 200 mL of deionized water, adding 40 mL of microcapsule core material obtained in step (3) to the TiO2 aqueous solution, and emulsifying the mixture at a speed of 800 r / min at room temperature for 1 h to obtain TiO2 emulsion;
[0056] (5) Preparation of microcapsule wall material: 10 g urea, 27 g formaldehyde and 200 mL deionized water were mixed, triethanolamine was added dropwise to adjust the pH to 8-9, and then heated in a water bath at 65° C. for 1 h to obtain a polyurea-formaldehyde prepolymer, and then 3 wt % of amphoteric TiO2 nanoparticles were dispersed in the polyurea-formaldehyde prepolymer by ultrasonic dispersion to obtain a TiO2-modified polyurea-formaldehyde prepolymer;
[0057] (6) adding 10 g of the TiO2 emulsion prepared in step (4), 1 g of ammonium chloride and 1 g of resorcinol to the TiO2-modified polyurea-formaldehyde prepolymer, adjusting the initial pH value to 4, and mechanically stirring at 900 r / min in a 60°C water bath for 4 h. After sufficient reaction, washing and filtering are performed to obtain microcapsules.
[0058] (7) beating and disintegrating the pulp sheet: soak 100 g of the pulp sheet in 6 L of deionized water for 6 h, tear the pulp sheet into small pieces, put it into a pulper, add deionized water for beating and decomposing, and after decomposing to a beating degree of 45° SR, put the pulp into a fiber disintegrator, add deionized water for mechanical treatment, so that the fibers are dispersed in water without changing their original structural properties, and obtain a pulp suspension;
[0059] (8) weighing microcapsules at a microcapsule doping concentration of 0.5 wt%, adding the microcapsules obtained in step (6) into 400 mL of deionized water, and dispersing them by magnetic stirring for 40 min, mixing the dispersed microcapsule aqueous solution with the pulp suspension, and stirring at 300 r / min for 15 min to obtain a microcapsule pulp suspension;
[0060] (9) degassing the microcapsule pulp suspension for 5 minutes and then pouring it into a pulp storage chamber, using a permanent magnet to attract the microcapsules to the upper surface of the microcapsule pulp suspension, keeping the magnet intact to prevent sedimentation, using a filter screen for molding, and vacuum drying the wet paper at 110° C. for 7 minutes. After balancing the moisture for 24 hours, a molded insulating paper hand sheet is obtained;
[0061] (10) The formed insulating paper hand sheet is placed in a calender for calendering treatment. The first stage of hot pressing is set at a temperature of 100° C. and a pressure of 1 MPa for 3 minutes; the second stage of hot pressing is set at a temperature of 160° C. and a pressure of 4 MPa for 10 minutes; the third stage of hot pressing is set at a temperature of 80° C. and a pressure of 2 MPa for 7 minutes to obtain the self-repairing cellulose insulating paper.
[0062] Example 2: This example is different from Example 1 in that the doping concentration of the microcapsules is 1 wt%.
[0063] Example 3: This example is different from Example 1 in that the doping concentration of the microcapsules is 2.5 wt%.
[0064] Example 4: This example is different from Example 1 in that the doping concentration of the microcapsules is 5 wt%.
[0065] Example 5: This example is different from Example 1 in that the doping concentration of the microcapsules is 10 wt%.
[0066] Example 6: This example is different from Example 1 in that microcapsules are not added to the pulp, thereby preparing traditional cellulose insulation paper.
[0067] Comparing the cellulose self-repairing insulating paper in the above example with the traditional cellulose insulating paper, the insulating paper prepared by the present invention has self-repairing ability compared with the unmodified insulating paper, which significantly improves the performance, safety and reliability of the insulating paper. The test results are shown in the attached figure.
[0068] As can be seen from the above embodiments and the accompanying drawings, the present invention provides a method for preparing self-repairing cellulose insulating paper doped with ultraviolet light-triggered microcapsules. The present invention adds prepared microcapsules during the pulping and papermaking process of insulating paper, and migrates the microcapsules using a directional magnetic field. Among them, epoxy acrylate (EA), neopentyl glycol diacrylate (NPGDA) and photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA) are used to synthesize the repair agent, and Fe3O4@SiO2 nanoparticles are added to modify the repair agent; urea and formaldehyde are mixed to synthesize the microcapsule wall material, and TiO2 nanoparticles are added to form a polyurea formaldehyde (PUF) / TiO2 hybrid shell. The present invention cleverly embeds a ultraviolet light-triggered microcapsule structure in cellulose to achieve active recognition and immediate self-repair of minor damage to the insulating paper. Once the material is damaged, the microcapsule ruptures to release the repair agent, which solidifies under ultraviolet light, thereby effectively filling and repairing the damage, significantly improving the durability and stability of the insulating paper. Due to the existence of the self-repair mechanism, the insulating paper can recover in time when facing minor damage, and also avoids the performance degradation caused by the expansion of damage, thereby substantially extending the service life of the insulating paper. By utilizing the navigation effect of Fe3O4@SiO2 nanoparticles, the insulating paper can also achieve a high degree of self-healing at low doping concentrations; the introduction of TiO2 nanoparticles effectively prevents the ultraviolet light of the repair agent from curing prematurely, ensuring its effective release when needed; at the same time, with the help of the in-situ ultraviolet light emitted by the electrically damaged tree branches to induce the curing of the healing agent, the braking identification of the insulating paper and the self-healing of the electrical damage of the insulating paper are realized. The self-repairing insulating paper of the present invention can better resist the continuous effects of factors such as electric fields and high temperatures, reduce the risks of local discharge and electric field distortion, and provide more reliable protection for the safe operation of the power grid. Compared with the overall replacement of traditional insulating paper after damage, the self-repairing insulating paper can reduce the frequency of material replacement and reduce the generation of waste materials. It also has significant self-repairing ability and self-repairing efficiency, which can effectively extend the service life and greatly reduce the risks caused by accidents such as insulation breakdown.
[0069] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules, characterized in that: The method comprises mixing paper pulp with microcapsules to prepare insulating paper, and migrating the microcapsules using a directional magnetic field; The microcapsules include a microcapsule core material and a microcapsule wall material. The microcapsule core material is made by modifying a repair agent with Fe3O4@SiO2 nanoparticles, and the microcapsule wall material is made by modifying a polyurea formaldehyde prepolymer with TiO2 nanoparticles. The repair agent includes epoxy acrylate, neopentyl glycol diacrylate, and a photoinitiator; The photoinitiator is 2,2-dimethoxy-2-phenylacetophenone.
2. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 1, characterized in that: The steps include: (1) Synthesis of Fe3O4 nanoparticles by hydrothermal reaction; (2) synthesizing Fe3O4@SiO2 nanoparticles, mixing the Fe3O4 nanoparticles with anhydrous alcohol, deionized water and ammonia water, ultrasonically treating the mixture, and then adding ethyl orthosilicate, and continuing the ultrasonic treatment. After the reaction is complete, washing and drying the mixture are performed to obtain Fe3O4@SiO2 nanoparticles; (3) preparing a microcapsule core material: dispersing the Fe3O4@SiO2 nanoparticles synthesized in step (2) in a repair agent for modification to obtain a microcapsule core material; (4) preparing TiO2 emulsion: adding the microcapsule core material obtained in step (3) into a TiO2 aqueous solution for emulsification to obtain a TiO2 emulsion; (5) Preparing microcapsule wall materials: urea, formaldehyde and deionized water are mixed, the pH is adjusted to 8-9, and then heated in a water bath to obtain a polyurea-formaldehyde prepolymer, and then amphoteric TiO2 nanoparticles are ultrasonically dispersed in the polyurea-formaldehyde prepolymer to modify it, thereby obtaining a TiO2-modified prepolymer; the concentration of the amphoteric TiO2 nanoparticles in the polyurea-formaldehyde prepolymer is 2-4wt%; (6) Preparing microcapsules: adding the TiO2 emulsion, ammonium chloride and resorcinol prepared in step (4) to the TiO2-modified polyurea-formaldehyde prepolymer, adjusting the pH value to 3.8-4.2, heating in a water bath and stirring until fully reacted, to obtain microcapsules; the mass ratio of the TiO2 emulsion, ammonium chloride and resorcinol is 9-12:0.8-1.2:0.8-1.2; (7) beating and dissociating the pulp sheet to obtain a pulp suspension; (8) mixing the microcapsules obtained in step (6) with a pulp suspension to obtain a microcapsule pulp suspension; (9) pouring the microcapsule pulp suspension into a pulp storage chamber, migrating the microcapsules to a target area under the action of a directional magnetic field, forming the microcapsules through a filter screen, and obtaining a formed insulating paper hand sheet by pressing and drying; (10) placing the formed insulating paper hand sheet into a calender for calendering to obtain the self-repairing cellulose insulating paper.
3. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 2, characterized in that: In the step (1), the hydrothermal reaction is specifically as follows: dissolving styrene sulfonic acid-maleic anhydride copolymer PSSMA, FeCl3·6H2O and NaAc in ethylene glycol, with the mass ratio of PSSMA:FeCl3·6H2O:NaAc being 1-2:1:1-2, stirring, and then transferring to a hydrothermal reactor to obtain Fe3O4 nanoparticles after sufficient reaction, and separating the synthesized Fe3O4 nanoparticles using a magnetic material after the hydrothermal reaction is completed.
4. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 2, characterized in that: In the step (4), the rotation speed is controlled at 600-1000 r / min during the emulsification treatment; and in the step (6), the mechanical stirring speed in the water bath is controlled at 800-1100 r / min.
5. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 1, characterized in that: The mass ratio of the epoxy acrylate, neopentyl glycol diacrylate and photoinitiator is 18-20:18-20:1-2.
6. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 2, characterized in that: In the step (2), the mass ratio of Fe3O4 to tetraethyl orthosilicate is 1:1-3, and the volume ratio of anhydrous alcohol, deionized water and ammonia water is 3.5-4.5:0.8-1.2:0.8-1.
2.
7. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 2, characterized in that: In the step (1), the concentration of FeCl3·6H2O is 0.2-0.5 mol / L, the concentration of NaAc is 0.2-0.5 mol / L, and the concentration of PSSMA is 0.1-0.5 mol / L.
8. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 2, characterized in that: In the step (10), the calendering treatment is a segmented hot pressing, and the specific steps include: The first stage of hot pressing: preheating stage, the temperature range is 80-120℃, the pressure is 0.5-2MPa, and the duration is 2-5min; The second stage of hot pressing: high temperature curing stage, the temperature is set at 140-180℃, the pressure is about 3-5MPa, and the duration is 5-15min; the third stage of hot pressing: cooling and shaping stage, the temperature gradually drops to 60-90℃, the pressure is maintained at 2-3MPa, and the duration is 5-10min.
9. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 2, characterized in that: In the step (8), the doping concentration of the microcapsules in the pulp suspension is 0.5-10 wt %.
10. The method for preparing self-repairing cellulose insulation paper doped with ultraviolet light-triggered microcapsules according to claim 2, characterized in that: In the step (3), the concentration of Fe3O4@SiO2 nanoparticles in the repair agent is 3-7wt%.
Citation Information
Patent Citations
Novel intelligent insulating material for realizing electrical tree damage self-healing and preparation method and application thereof
CN114891318A
Self-healing aramid fiber laminated paper and preparation method thereof
CN118686017A
Cellulose nanocrystal reinforced phase-based insulation paper self-healing network construction method
CN118814524A
Microcapsule having self-healing and conducting property, self-healing fiber and method for preparing the same
KR1020160140273A